Observation, theory and modeling of atmospheric variability : Selected papers of Nanjing Institute of Meteorology Alumni in commemoration of Professor Jijia Zhang / Xun Zhu...[và những người khác] - Ming, Cai
ĐTTS ghi: World Scientific series on meteorology of East Asia, v. 3